Effects of climatic factors towards bagworm population in oil palm plantation site / Norhanisah Norjim - Norjim, Norhanisah (Faculty of Plantation and Agrotechnology, 2017)
Oil palm (Elaeis guineensis) is known to be one of the important crops that contribute on developing the economic sectors in Malaysia. As the productions of Fresh Fruit Bunches (FFB) depend on the number of fronds that exists on the palm, it is a compulsory for the personnel in the plantation to maintain the stability of the FFB production. The main problem is the reduction of productivity rate has become serious due to the leaf-eating pest which is known as bagworm (Metisa plana). M. plana is known to be a problematic pest which causes declination of productivity rate as they feed on the leaves and create their nest on the oil palm fronds which lead to skeletonization of the oil palm. It is said that the population outbreak of M. plana is related to climatic factors such as temperature, humidity, rainfall and other factors that relate to climatic issues. As the previous researcher has done numerous of study that involve climatic factors towards M. plana population, different kinds of method were being used in order to test whether the population have been affected by the climatic factor or vice versa by using different kinds of analysis and sampling method such as mating behavior, development stage, and observations through constant temperature cabinet. This review paper focuses on reviewing various articles on the relationship of bagworm with the climatic factors. It highlights important aspect that will contribute in management of bagworm in oil palm. The findings show that M. plana has the tendency to reduce their populations when the temperature is below 15°C or above 40°C where the most favorable temperature for their population growth is around 25°C to 35°C with the relative humidity is around 92%-93% RH. Other than that, the rainfall factor also affect the population based on the rainfall volume and frequencies that happen on a certain locations where the population may be washed-off if the amount of rainfall exceed 200mm per month but still the outbreak may be happen if the site is poorly manage by the plantation workers. For example lack of proper pruning practice in the site. The plantation personnel must be alert with the management practice in order to control the population outbreak of M. plana despite any climactic factors.